Directed energy deposition (DED) of Inconel 718-SS316 L bimetallic structures: Experimental investigations and optimization through artificial humming bird algorithm for improved high strain rate and mechanical properties - D. Rajamani; A.R. Vinod; K. Niranjan Reddy; M. Siva Kumar (Results in Engineering)
The present work investigates the influence of direct energy deposition (DED) based additive manufacturing (AM) parameters on the high strain rate and mechanical properties of Inconel 718-SS316 L bimetallic structures fabricated at different processing conditions. The bimetallic structures were fabricated based on the box-behnken design methodology by varying the most significant DED parameters such as laser power (300–500 W), scanning speed (300–500 mm/min) and powder feedrate (3–4 g/min). Influence of these parameters on the high strain rate behaviour and microhardness were assessed through statistical analysis using analysis of variance (ANOVA) and three-dimensional response surface plots. Optimal DED parameters for improved response characteristics were attained through a metaheuristic-based hummingbird algorithm. The microstructural investigations including metallographic analysis, scanning electron microscope (SEM) with elemental dispersive spectroscopy (EDS) analysis and electron backscattered diffraction (EBSD) analysis were performed at the intermetallic regions of bimetallic samples which were fabricated at optimal processing conditions and the mechanical fractured surfaces. This study reveals the insights into the development of bimetallic structures through DED process with their microstructures, process-property relationship and multi-response optimization through metaheuristic algorithms concerning the improved high strain rate and mechanical characteristics.